2013
DOI: 10.1371/journal.pone.0062559
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Represses the GD3 Synthase Gene ST8SIA1 Expression in Human Breast Cancer Cells by Preventing NFκB Binding to ST8SIA1 Promoter

Abstract: Recent data have underlined a possible role of GD3 synthase (GD3S) and complex gangliosides in Estrogen Receptor (ER) negative breast cancer progression. Here, we describe the main transcript of the GD3S coding gene ST8SIA1 expressed in breast tumors. We characterized the corresponding core promoter in Hs578T breast cancer cells and showed that estradiol decreases ST8SIA1 mRNA expression in ER-positive MCF-7 cells and ERα-transfected ER-negative Hs578T cells. The activity of the core promoter sequence of ST8SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
2
32
0
1
Order By: Relevance
“…Thus, the TNF-mediated regulation of G D3 and G D2 previously described could involve the NF-κB pathway, which promotes proliferative and prosurvival gene expression; and has been implicated in EMT, the process by which cancer cells become more invasive and acquire metastatic potential [106]. Interestingly, our studies recently demonstrated that TNF induces up-regulation of the GD3S gene expression in ER-negative breast cancer cells via NF-κB transcription factor while in ER-positive cells, estradiol represses the TNF-induced up-regulation of GD3S by inhibiting NF-κB nuclear translocation (Figure 4) [105]. This result could explain the higher expression of GD3S in ER-negative breast cancer cells and allows a better understanding of the molecular mechanism leading to the regulation of gangliosides expression by cytokines.…”
Section: Regulation Of Ganglioside Expression By Pro-inflammatory mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the TNF-mediated regulation of G D3 and G D2 previously described could involve the NF-κB pathway, which promotes proliferative and prosurvival gene expression; and has been implicated in EMT, the process by which cancer cells become more invasive and acquire metastatic potential [106]. Interestingly, our studies recently demonstrated that TNF induces up-regulation of the GD3S gene expression in ER-negative breast cancer cells via NF-κB transcription factor while in ER-positive cells, estradiol represses the TNF-induced up-regulation of GD3S by inhibiting NF-κB nuclear translocation (Figure 4) [105]. This result could explain the higher expression of GD3S in ER-negative breast cancer cells and allows a better understanding of the molecular mechanism leading to the regulation of gangliosides expression by cytokines.…”
Section: Regulation Of Ganglioside Expression By Pro-inflammatory mentioning
confidence: 99%
“…All together these data indicate that the regulation of ganglioside content by cytokines is closely related to the regulation of the GTs involved in ganglioside biosynthesis. In this prospect, the transcriptional regulation of GD3S gene ( ST8SIA1 ), the key enzyme involved in the biosynthesis of b-and c-series gangliosides, has been well described in melanoma, neuroblastoma and breast cancer cells; highlighting a crucial role of NF-κB in activating this gene [103,104,105]. Thus, the TNF-mediated regulation of G D3 and G D2 previously described could involve the NF-κB pathway, which promotes proliferative and prosurvival gene expression; and has been implicated in EMT, the process by which cancer cells become more invasive and acquire metastatic potential [106].…”
Section: Regulation Of Ganglioside Expression By Pro-inflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic control is supposed to be relevant in many cases [47,48], while other emerging mechanisms controlling gene expression, such as the presence of regulatory RNA sequence and or RNA binding proteins [49], are, as yet, unexplored. At present, data are available about promoter sequences and potential regulatory elements operating in various tissues [50,51,52,53,54,55,56,57], while those actually involved in gastrointestinal cancer are described in very few cases [43,58,59,60,61]. This is a very promising field of research since a bidirectional relationship may exist between the expression of sLe antigens and the mechanisms controlling cell growth.…”
Section: Regulation Of Slea and Slexmentioning
confidence: 99%
“…On the other hand, analysis of cell surface gangliosides in melanocytes incubated with TNF shows a higher expression of GM3 and GD3 [22]. Interestingly, TNF induces up-regulation of the GD3 synthase gene expression in ER-negative breast cancer cells via NFκB transcription factor, while in ER-positive cells, estradiol represses the TNF-induced up-regulation of GD3 synthase by inhibiting NFκB nuclear translocation [23]. Finally, GTs involved in the synthesis of gangliosides can be also regulated by post-translational modifications such as phosphorylation and dephosphorylation [24,25].…”
Section: Introductionmentioning
confidence: 98%